EFEKTIVITAS PENGAWASAN CAMAT DALAM PENYELENGGARAAN PEMERINTAHAN DESA DI KECAMATAN TALAWAAN KABUPATEN MINAHASA UTARA - TAKBIR, FIRGINIA LITA; Londa, Very; Tampongangoy, Deysi (Sam Ratulangi University, 2016)
ABSTRACT: The purpose of this study was to determine the effectiveness of the supervision of theHead of administration of the village in the district Talawaan North Minahasa regency. Research usingqualitative methods. The informants were 12 people consisting of: Head, Head of Governments of theDistrict, 3 Village Head, 3 administrators BPD, and 3 administrators LPMD.Collecting data with interview techniques; while the data were analyzed using qualitative analysistechniques interactive model of Miles and Hubernann.Based on the results of the study it can be concluded: (1) Control Head of the administration of thevillage in the district of North Minahasa Regency Talawaan effective enough views of things: thesupervision of the preparation and implementation of regulations and rules village head; supervisionorderly implementation of village administration; Supervising the management of village finances;supervising the implementation of the tasks and performance of the village head and village; supervision ofthe implementation of the tasks and functions of BPD; supervision of the implementation of tasks andfunctions LPMD; means / measures to evaluate the administration of the village; means / measurescorrecting irregularities in the administration of the village administration. (2) Control Head can realizeEffectiveness village governance.Based on the conclusion of the study suggested: (1) Head should be more exercise directsupervision that is down to the villages to monitor and evaluate the direct administration of the village. (2)Control Head in governance be of more preventive village.Keywords: Effectiveness, Oversight, Village Government.